2013
DOI: 10.1080/10615806.2013.839988
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive processes as mediators of the relation between mindfulness and change in social anxiety symptoms following cognitive behavioral treatment

Abstract: The present study examined whether pretreatment mindfulness exerts an indirect effect on outcomes following cognitive-behavioral therapy (CBT). Cognitive processes of probability and cost bias (i.e., overestimations of the likelihood that negative social events will occur, and that these events will have negative consequences when they do occur) were explored as potential mediators of the relation between mindfulness and social anxiety symptom change. People with higher levels of mindfulness may be better able… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 56 publications
2
7
0
Order By: Relevance
“…Cognitive behavioral conceptualizations of SAD may benefit from integrating constructs aligned with alternative treatments. For example, researchers have begun to examine the role of trait mindfulness in CBT for SAD [75]. One study found that cognitive restructuring and mindfulness strategies together reduced post-event processing, a ruminative and anxiety-maintaining cognitive process common among individuals with SAD, and improved affect [76].…”
Section: Cognitive Behavioral Therapymentioning
confidence: 99%
“…Cognitive behavioral conceptualizations of SAD may benefit from integrating constructs aligned with alternative treatments. For example, researchers have begun to examine the role of trait mindfulness in CBT for SAD [75]. One study found that cognitive restructuring and mindfulness strategies together reduced post-event processing, a ruminative and anxiety-maintaining cognitive process common among individuals with SAD, and improved affect [76].…”
Section: Cognitive Behavioral Therapymentioning
confidence: 99%
“…Dispositional mindfulness has also been found to be negatively correlated with engagement in intuitive thinking ( Remmers et al, 2014 ). In light of recent research suggesting a link between mindfulness, self-regulation, and EF ( Feltman et al, 2009 ; Tang and Posner, 2009 ; Sahdra et al, 2011 ; Moore et al, 2012 ; Lyvers et al, 2013 ; Morgan et al, 2013 ; Ostafin et al, 2013a ) and work suggesting a link between self-regulation, EF, and CT performance ( West et al, 2008 ; Sanz de Acedo Lizarraga et al, 2012 ; Evans and Stanovich, 2013 ; Dwyer et al, 2014 ), the current study sought to investigate whether the relationship between dispositional mindfulness and CT performance is mediated by EF performance.…”
Section: Introductionmentioning
confidence: 99%
“…Summary scores were generated by averaging the items within each scale, with higher values reflecting greater probability or cost of negative events. Consistent with previous findings (Morgan et al, 2014;Uren et al, 2004;Weeks et al, 2016), high internal consistencies were found for the social subscales of both the OPQ (α = .91) and the OCQ (α = .94).…”
Section: Aims and Hypothesessupporting
confidence: 91%